Planar wiggler as a tool for generating hard twisted photons; Journal of Instrumentation; Vol. 15 : Radiation from Relativistic Electrons in Periodic Structures (RREPS-19) - Bogdanov O. V. Oleg Viktorovich (2020, 2020)
Title screen